2023
DOI: 10.1029/2022ef003211
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Large‐Scale Meteorological Patterns to Extratropical Cyclones in CMIP6 Climate Models Using Self‐Organizing Maps

Michelle J. Gore,
Colin M. Zarzycki,
Melissa M. Gervais

Abstract: Extratropical cyclones (ETCs) are responsible for the majority of cool‐season extreme events in the northeastern United States (NEUS), often leading to high‐impact weather conditions that can have wide‐ranging socioeconomic impacts. Evaluating the ability of climate models to adequately simulate ETC dynamics is essential for improving model performance and increasing confidence in future projections used by stakeholders and policymakers. ETCs are traditionally studied using techniques such as case studies and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…These investigations aimed to improve climate modeling by assessing the accuracy of model simulations. SOMs were employed by Gore et al [27] to establish connections between large-scale meteorological patterns and extratropical cyclones in CMIP6 climate models. This study demonstrated the capability of SOMs in linking meteorological patterns to cyclones.…”
Section: Introductionmentioning
confidence: 99%
“…These investigations aimed to improve climate modeling by assessing the accuracy of model simulations. SOMs were employed by Gore et al [27] to establish connections between large-scale meteorological patterns and extratropical cyclones in CMIP6 climate models. This study demonstrated the capability of SOMs in linking meteorological patterns to cyclones.…”
Section: Introductionmentioning
confidence: 99%